Interferometric measurement of refractive index change of tumor cells under electrical fields - (:unkn) unknown (The Optical Society, 2020)
This work proposes an interferometric method to simultenously measure the refractive index change and thickness of live cells under applied electrical fields. It may allow practical and accurate assessment of intracellular response to electrical stimulation. © 2020 The Author(s)